POLITICAL PROCESSES IN KOSOVO AND METOHIJA IN A COMPARATIVE-HISTORICAL PERSPECTIVE (Heritage, 2020)
The paper discusses the issue of political processes in Kosovo and Metohija in a comparative historical perspective. We consider the historical vertical line of processes that followed the political situation of the Serbian people in this area, as well as political processes and events that have marked the contemporary crisis in Kosovo.
Keywords: Kosovo and Metohija, Serbia, history, political processes, Serbs, Albanians